2012
DOI: 10.1371/journal.pone.0029735
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Asymmetrical Cytokinesis by cAMP during Meiosis I in Mouse Oocytes

Abstract: Mammalian oocytes undergo an asymmetrical first meiotic division, extruding half of their chromosomes in a small polar body to preserve maternal resources for embryonic development. To divide asymmetrically, mammalian oocytes relocate chromosomes from the center of the cell to the cortex, but little is known about the underlying mechanisms. Here, we show that upon the elevation of intracellular cAMP level, mouse oocytes produced two daughter cells with similar sizes. This symmetrical cell division could be res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 72 publications
2
11
0
Order By: Relevance
“…Thus, it can be inferred that PRKAR2B plays an important role in oocyte division. These results are consistent with previous reports that various factors, including PKA family proteins, play an important role in cell division of the oocyte meiosis stage [36, 37]. We also confirmed that PRKAR2B deficiency [38] results in division failure of the oocyte, as determined using time lapse video recording for 36 h (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, it can be inferred that PRKAR2B plays an important role in oocyte division. These results are consistent with previous reports that various factors, including PKA family proteins, play an important role in cell division of the oocyte meiosis stage [36, 37]. We also confirmed that PRKAR2B deficiency [38] results in division failure of the oocyte, as determined using time lapse video recording for 36 h (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Oocytes treated with a single MAM reagent had larger PB1, this was consistent with previous results showing that the single use of dbcAMP, IBMX, or forskolin generated abnormal PB1 due to failed spindle migration (Chen et al, 2012). A high incidence of apoptosis is associated with a reduction in oocyte quality Wu et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, substantial evidence indicates that long‐term artificial MAM in oocytes by a single reagent induces unwanted adverse effects on the development potential of subsequent oocytes. For example, the artificial elevation of intracellular cAMP levels by dbcAMP or IBMX leads to a giant first polar body (PB1) in mice due to abnormal chromosome migration (Chen et al, 2012). Delayed oocyte maturation has been observed when forskolin or IBMX is used to maintain the GV stage in sheep (Buell, Chitwood, & Ross, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stagnation of oocyte meiosis depends on high concentrations of second messenger cAMP (Chen et al, 2012) while the desired cAMP maintaining meiotic stagnant is produced by the oocyte itself (Liu et al, 2013). cAMP dependent protein kinase A inhibits maturation promoting factor (MPF) activity.…”
Section: Discussionmentioning
confidence: 99%